Applications of Artificial Intelligence in Academic Libraries - Vijayakumar, S; Sheshadri, KN (International Journal of Computer Sciences and Engineering, 2025)
The application of artificial intelligence involves the areas such as artificial intelligence, expert system, artificial neural network, fuzzy logic, image processing, natural language processing, speech recognition, robotics etc. Though these areas are not separate, at times two or more applications are contributes to enrich the library services. In this article, the authors have explored the various possible applications of artificial intelligence as mentioned above. In addition, authors explain the possible areas where few of these applications can be implemented which enhances the quality of services and thereby create the potential impact of AI on library services.